Nivolumab for Metastatic Cutaneous Squamous Cell Carcinoma - Marcos Oro-Ayude; Hae Jin Suh-Oh; Victor Sacristán-Santos; Patricia Vázquez-Bartolomé; Ángeles Flórez (Karger Publishers, 2020)
Nivolumab is a programmed death receptor 1 (PD-1) inhibitor. It is part of a group of drugs known as immune checkpoint blockers, which enable potent and durable T-cell responses against several tumors. We report the case of a patient with a metastatic squamous cell carcinoma, who is being treated with nivolumab. This patient achieved a complete response and continues treatment without progression signs, supporting the notion that PD-1 inhibition can induce long-term remission and is well tolerated in this type of patient.